ANALISIS RASIO AKTIVITAS TERHADAP KEMAMPUAN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Nur Aini Qaidah; Sri Wahyuti (University of Widya Gama Mahakam Samarinda, 2021)
The purpose of this study was to determine the effect of total asset turnover ratio, accounts receivable turnover ratio and inventory turnover ratio on profitability in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2013-2017 period. The method in this research is correlational quantitative. The measuring instrument uses the Total Asset Turnover Ratio, Account Receivable Turnover Ratio and Return On Investment. The sampling technique is purposive sampling. The sample is 10 companies listed in the food and beverage sector on the Indonesia Stock Exchange with data from 2013-2017. The analysis of this research uses multiple linear regression analysis. The results of the study show the effect of total asset turnover ratio, accounts receivable turnover ratio and inventory turnover ratio simultaneously on profitability. Total asset turnover ratio has a negative and insignificant effect on the profitability of food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. Accounts receivable turnover ratio has a negative and insignificant effect on the profitability of food and beverage sector companies listed on the Indonesia Stock Exchange for the 2013-2017 period. Inventory turnover ratio has a positive and significant effect on the profitability of food and beverage sector companies listed on the Indonesia Stock Exchange for the 2013-2017 period.